Unsurrendered : a global health challenge the story of Philippine guerillas and bolomen - Morales, Tea; Salalima, Rodolfo A.; Marzan, Renato O.; Asuncion, Elvi John; Parsons, Peter; Cavett, Morgan; Guillermo, Lucky; Villadares, Rex Vincent; Williams, Michael (Spyron AV Manila Productionst, 2009)
Story of the Philippine guerillas as told by 100 voices. Filipino-American armed forces were sadly under-prepared for war when Japan attacked both Pearl Harbor and the Philippine in December 1941. A spontaneous resistance movement sprang up throughout the islands among Filipino civilians of all ages and sexes, and among the American and Filipino soldiers who remained unsurrendered or who escaped imprisonment after the falls of Bataan and Corregidor. It is about spontaneous movement that sprung up all over the Philippines when the Japanese imperial army invaded the Philippines in 1941.